Sensitifitas dan Spesifisitas Teknik Imunohistokimia Rabies - Wirata, I Ketut; Berata, I Ketut; Puja, I Ketut (Veterinary Science and Medicine Journal; Vol 2 No 1 (2014), 2014)
Fluorescent Antibody Test (FAT) is a golden standard for rabies diagnosis, but it requires many sample preconditions before testing. Immunohistochemical technique (IHC) has the same principle as the FAT, however, it is more simple. This study was conducted to examine the sensitivity and specificity of IHC compare to FAT. The sensitivity and specificity were calculated using the formula of 2 x 2 contingency table and statistical analysis of the chi-square. Out of 40 samples that rabies positive on FAT, 27 samples (67.5%) showed rabies positive on IHC and 13 samples (32.5%) showed rabies negative on IHC. All samples that rabies negative on FAT were also rabies negative on IHC. The IHC has the sensitivity and specificity level 67.5% and 100% respectively. The IHC has a lower sensitivity than FAT, however, IHC has many advantages such as it can be performed on formalin fixed-samples. A further research is necessary to improve the sensitivity of IHC on detecting the rabies.
Keywords: rabies; dog; sensitivitas; FAT; IHC